PH-Dependent Multistate System Generated by a Synthetic Furanoflavylium Compound: An Ancestor of the Anthocyanin Multistate of Chemical Species - Alejo-Armijo, A. (2019)
This work was supported by the Associate Laboratory for Green Chemistry-LAQV, which is financed by national funds from FCT/MCTES (UID/QUI/50006/2019). FCT/MCTES is also acknowledged through the National Portuguese NMR Network RECI/BBB-BQB/0230/2012. A.A.-A. is grateful for the postdoctoral fellowship from Fundacion Alfonso Marti0n Escudero.